An insight into molecular taxonomy of bufonids, microhylids, and dicroglossid frogs: First genetic records from Pakistan. Issue 20 (28th September 2021) - Akram, Ayesha; Rais, Muhammad; Lopez‐Hervas, Karem; Tarvin, Rebecca D.; Saeed, Muhammad; Bolnick, Daniel I.; Cannatella, David C.
Abstract: The current study was focused on documentation of amphibian assemblage in North Punjab and Islamabad Capital Territory, Pakistan, by using mitochondrial gene sequences of 16S rRNA. Our study entailed 37% of the known amphibian species of the country. We provided a phylogenetic analysis based on 74 newly generated mitochondrial 16S rRNAs from nine species of genus Microlyla, Duttaphrynus, Allopaa, Nanorana, Sphaerotheca, Minervarya, Hoplobatrachus, and Euphlyctis . We employed the maximum‐likelihood inference and Bayesian analysis to assess the taxonomic status of the samples obtained from Pakistan, with respect to other congeneric species from surrounding regions. Our findings confirmed the taxonomic status of South Asian anuran species Duttaphrynus stomaticus, Duttaphrynus melanostictus, Microhyla nilphamariensis, Allopaa hazarensis, Nanorana vicina, Sphaerotheca maskeyi (synonym : S. pashchima), Minervarya pierrei, Hoplobatrachus tigerinus, and Euphlyctis kalasgramensis in Pakistan. We have reported new country records of genus Minervarya ( M . pierrei ). Minervarya pierrei was previously misidentified as Fejervarya limnocharis, due to dearth of genetic information. We provided the first genetic records of our endemic species N . vicina . The results revealed the taxonomic placement of N . vicina with respect to its congeners and validated the taxonomic status of N . vicina from its type locality (Murree) for the first time. The findings of the present study also indicated the paraphyletic relationship of A.‐ hazarensis with Nanorana species. So, based on our phylogenetic inferences, morphological characters, and habitat preferences, validity of generic status of A . hazarensis is undecided. As our data were not enough to resolve this issue, we suggest sequencing of additional mitochondrial and nuclear genes in the future studies to get a better resolution. We recommend carrying out extensive surveys throughout the country for proper scientific documentation of amphibians of Pakistan. Many new species, some of them might be endemic to Pakistan, are expected to be discovered, and taxonomic status of other species would be resolved. Abstract : The current study was focused to document amphibian assemblage of North Punjab and Islamabad Capital Territory, Pakistan, by using 16S rRNA. Our findings on the taxonomic status of South Asian anuran species confirmed the presence of Duttaphrynus stomaticus, Duttaphrynus melanostictus, Microhyla nilphamariensis, Sphaerotheca maskeyi (synonym: S. pashchima ) Hoplobatrachus tigerinus, Euphlyctis kalasgramensis and Allopaa hazarensis . We have reported new country records of Minervarya pierrei and reported the first genetic records of south asian endemic species Nanorana vicina from its type locality.